2017
DOI: 10.1590/1980-5373-mr-2017-0553
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electronic Structure and Optical Performance of Bi2Te3-xSex From First-principle Calculations Within TB-mBJ Exchange Potential

Abstract: Using the first-principle calculations of density functional theory within the (FP-LAPW) method, we have investigated the structural, electronic and optical properties of Bi 2 Te 3-x Se x alloys with compositions x = 0, 1, 2 and 3 of Se. The generalized gradient approximation functional of Wu and Cohen (GGA-PBE) is used to calculate ground state structural parameters of Bi 2 Te 3-x Se x , which are in good agreement with theoretical and experimental data. The electronic band structures and optical constants ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The maximum of 38-45% light is likely to be reflected at the peak positions around 2.1 eV, and it is 15-25% around the onset of absorption. The reflectivity spectra of other systems reported elsewhere have similar characteristics (Peng et al, 2013;Ma et al, 2014;Saini et al, 2017;Mohamed et al, 2018). The energy loss function is plotted in Figure 5D.…”
Section: Optical Propertiessupporting
confidence: 71%
“…The maximum of 38-45% light is likely to be reflected at the peak positions around 2.1 eV, and it is 15-25% around the onset of absorption. The reflectivity spectra of other systems reported elsewhere have similar characteristics (Peng et al, 2013;Ma et al, 2014;Saini et al, 2017;Mohamed et al, 2018). The energy loss function is plotted in Figure 5D.…”
Section: Optical Propertiessupporting
confidence: 71%
“…Optoelectronic Performance in the Visible Region. Owing to the broadband light absorption of Bi-and Sb-based TIs, 21,36 our Bi 2 SeTe 2 photodetector demonstrates excellent photoresponse behavior throughout the visible region. First, we measured the I ds − V ds characteristics of the device with the shorter channel length of 3 μm under different illumination wavelengths and power densities (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Further spectral photoresponse analysis finds that the Bi photodetector exhibits a relatively weak sensitivity to 488 nm illumination because of an oscillation in the absorption of Bi 2 SeTe 2 in the corresponding energy range. 21 The observed responsivity, which is 1 order of magnitude higher than for most individual TI-based self-biased photodetectors to date, coupled with the response time shorter than 40 ms, makes the photodetector one of the quickest among devices based only on topological insulators.…”
Section: Introductionmentioning
confidence: 99%
“…Berber Mohamed et al have reported that Bi 2 Te 3Àx Se x alloys are coveted recruits for optoelectronic application in the infrared and visible regions. 23 According to Hongliang Shi et al, Bi 2 Te 2 Se and Bi 2 Te 3 have complex band structures, particularly non-parabolic isoenergy surfaces, which are advantageous for obtaining highperformance thermoelectrics. 24 The performance of photodetection can be enhanced by using heterostructures with 2D materials and TIs.…”
Section: Introductionmentioning
confidence: 99%